The Influence of the Binder Type & Aggregate Nature on the Electrical Resistivity and Compressive Strength of Conventional Concrete - Deda, Hugo (Université d'Ottawa / University of Ottawa, 2020)
Concrete has been used in a number of civil engineering applications due to its interesting fresh, hardened, and durability-related properties. 28-day compressive strength is the most important hardened state property and is frequently used as an indicator of the material’s quality. However, early-age mechanical properties are a key factor nowadays to enhance construction planning. Several advanced techniques have been proposed to appraise concrete microstructure and quality, and among those electrical resistivity (ER) is one of the most commonly used since it is a non-destructive and low-cost technique. Although recent literature data have shown that ER may be significantly influenced by a variety of parameters such as the test setup, material porosity and moisture content, binder type/amount and presence of supplementary cementing materials (SCMs) along with the nature of the aggregates used in the mix, further research must be performed to clarify the influence of the raw materials (i.e. SCMs and aggregate nature) on ER using distinct setups. Therefore, this work aims to appraise the influence of the coarse aggregate nature and binder replacement/amount on the concrete ER and compressive strength predictions models through ER. Twenty-four concrete mixtures were developed with two different coarse aggregate natures (i.e. granite and limestone), two different water-to-binder ratios (w/b; i.e. 0.6 and 0.4) and incorporating two different SCMs (i.e. slag and fly-ash class F) with different replacement levels. Moreover, three distinct ER techniques (e.g. bulk, surface, and internal) and compressive strength tests were performed at different ages (i.e. 3, 7, 14, and 28 days). Results indicate that the binder type and replacement amount significantly affect ER and compressive strength. Otherwise, the coarse aggregate nature presented only trivial influence for 0.6 w/b mixes, except for 50% fly-ash replacement samples; whereas for concrete specimens with enhanced microstructure (i.e. 0.4 w/b), the aggregate nature influence was statically significant especially for the binary mixtures with high SCMs replacement levels (i.e. 70% GGBS and 50% fly-ash). Finally, all ER test setups were considered to be quite suitable and reliable NDT techniques correlating themselves very well. Yet the internal resistivity setup demonstrated to be the device which yields the lowest variability amongst them.
Keywords: Electrical resistivity; Non-destructive testing; Concrete microstructure; Supplementary cementitious materials